Perceptions of injectable therapies with cardiovascular benefit: an ACNAP survey of healthcare professionals to explore facilitators and barriers - Khatib, Rani; Angus, Neil J.; Hansen, Tina B; Lambrinou, Ekaterini; Vellone, Ercole; Khan, Mutiba; Lee, Geraldine A. (My University, 2022)
Injectable medicines are increasingly used to manage risk factors for cardiovascular (CV) events, such as dyslipidaemia and diabetes. These include proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors and glucagon-like peptide-1 (GLP-1) receptor agonists. Little is known about perceptions of injectable therapies among CV healthcare professionals (HCPs). This study explores their views to identify relevant facilitators and barriers to the use of injectables with CV benefit.
Keywords: Adherence; GLP-1 receptor agonist; Healthcare professionals; Injectable; PCSK9 inhibitor; Survey